KRISIS PERKAWINAN KATOLIK DI PAROKI SANTO YOSEF PEKERJA WAIRPELIT DARI PERSPEKTIF SERUAN APOSTOLIK AMORIS LAETITIA - Vinsensius M. Junior Situmorang (STP St. Bonaventura Medan, 2025)
This abstract aims to analyze the Catholic marital crisis in the Paroki Santo Yosep Pekerja Wairpelit, in light of the Apostolic Exhortation Amoris Laetitia, and to formulate a contextual family pastoral model. This study uses a qualitative method with a field approach through in-depth interviews with relevant parties. The research stages include understanding the purpose of Catholic marriage, identifying marital problems, examining Pope Francis's views on love in marriage according to Amoris Laetitia, analyzing the marital crisis using a contextual pastoral approach, and developing recommendations for family pastoral measures. The results of the study indicate that a number of couples in the Parish of Saint Joseph the Worker, Wairpelit, are experiencing marital crises caused by internal and external factors such as declining love, infertility, economic difficulties, lack of communication, and work commitments. These factors impact the harmony and stability of the household. Based on these findings, a more contextual family pastoral model is needed, rooted in the spirit of Amoris Laetitia, and emphasizing humane, compassionate, and relevant family care. The Church is expected to be present as a community that supports and strengthens couples in realizing their calling to married life with joy and new hope.